Efficacy of commercial vaccines against newly emerging avian influenza H5N8 virus in Egypt - Kandeil, Ahmed; Sabir, Jamal S. M.; Abdelaal, Ahmed; Mattar, Ehab H.; El-Taweel, Ahmed N.; Sabir, Mumdooh J.; Khalil, Ahmed Aly; Webby, Richard; Kayali, Ghazi; Ali, Mohamed A. (Scientific reports, 2018)
The newly emerging, highly pathogenic avian influenza (HPAI) H5N8 virus of clade 2.3.4.4 was recently detected in wild birds and domestic poultry in Egypt in the 2016/2017 winter season. Vaccination based on commercial H5 vaccines is used as an essential control strategy in Egyptian poultry. Here, we studied the efficacy of the eight most common commercial H5 poultry vaccines in the Egyptian market and compared them with an experimental vaccine based on the Egyptian LPAI H5N8 virus that was prepared by using reverse genetics. The experimental vaccine and Re-5 commercial vaccine were able to completely protect chickens and significantly reduce virus shedding. Our results indicate that most of the commercial poultry H5 vaccines used in the present study were ineffective because the seed viruses in these vaccines are genetically distinct from the H5N8 viruses currently circulating in Egypt. Although some of the commercial vaccines protected chickens from mortality, they failed to prevent chickens from shedding the virus. Accordingly, we recommend updating and reinforcing the H5N8 prevention and control strategies in Egypt. The vaccination strategy should be reconsidered based on currently circulating viruses.